Nistawatsiman: Rethinking Assessment of Aboriginal Parents for Child Welfare Following the Truth and Reconciliation Commission - Lindstrom, Gabrielle; Choate, Peter (First Peoples Child & Family Review, 2016)
The Truth and Reconciliation Commission report has challenged Canada to alter the relationship with Aboriginal peoples across the country. They have specifically identified child protection as one area that requires a significant reconsideration around how agencies charged with this responsibility interact with Aboriginal people both on and off reserves. The legacy of Residential Schools, the Sixties Scoop and other policies of assimilation and cultural genocide are found in a number of existing social policy and practices, including child protection. This work examines the depth of change that will be needed in child protection methodologies by challenging the current assessment practice which seeks to determine, from a Western child-rearing perspective, if parents are ‘good enough’ to raise their children. The project shows the depth of disparities between present and historical practices and Aboriginal culture, using reference to the Blackfoot Confederacy in southern Alberta. The project draws upon a broad literature review as well as an expert consultation with six traditional Blackfoot Elders.